Population pharmacokinetics of the antimalarial amodiaquine: A pooled analysis to optimize dosing - Ali, A; Penny, M; Smith, T; Workman, L; Sasi, P; Adjei, G; Aweeka, F; Kiechel, J; Jullien, V; Rijken, M; McGready, R; Mwesigwa, J; et al. (American Society for Microbiology, 2018)
Amodiaquine plus artesunate is the recommended antimalarial treatment in many malaria-endemic countries. However, pediatric doses are largely based on a linear extrapolation from adult doses. We pooled data from previously published studies on the pharmacokinetics of amodiaquine, to optimize the dose across all age groups. Adults and children with uncomplicated malaria received daily weight-based doses of amodiaquine or artesunate-amodiaquine over three days. Plasma concentration-time profiles for both parent drug and metabolite were characterized using nonlinear mixed-effects modelling. Amodiaquine pharmacokinetics was adequately described by a two-compartment disposition model, with first-order elimination leading to the formation of desethylamodiaquine, which was best described by a three-compartment disposition model. Body size and age were the main covariates affecting amodiaquine clearance. After adjusting for the effect of weight, clearance rates for amodiaquine and desethylamodiaquine reached 50% of adult maturation at 2.8 (95% CI: 1.5 - 3.7) and 3.9 (95% CI: 2.6 - 5.3) months after birth, assuming a baby born at term. Bioavailability was 22.4% (15.6 - 31.9%) lower at the start of treatment than during convalescence, which suggests a malaria disease effect. Neither drug formulation nor hemoglobin had an effect on any pharmacokinetic parameters. Results from simulations showed that current manufacturer dosing recommendations resulted in low desethylamodiaquine exposure in patients weighing 8 kg, 15 - 17 kg, 33 - 35 kg, and in patients > 62 kg compared to a typical 50 kg patient. We propose possible optimized dosing regimens to achieve similar drug exposures among all age groups, which require further validation.